Maternal employment, childcare and childhood overweight during infancy - Thérèse McDonnell; Orla Doyle (University College Dublin, UCD School of Economics, 2014)
This paper examines the relationship between maternal employment, childcare during infancy and the overweight status of pre-school children. Using data from the Infant Cohort of the Growing-Up in Ireland Survey, propensity score matching addresses the issue of potential selection bias, quantile regression allows the impact of both maternal employment and childcare to be examined throughout the weight distribution and multiple imputation is used to address the problem of missing data due to item non-response. The results suggest that both full-time and part-time maternal employment when a child is 9 months old increase the likelihood of being overweight at 3 years old, but only for children of mothers with higher levels of education. Informal childcare at 9 months also has harmful effects on child weight, but again only for children of more educated mothers. Quantile regression finds that the children most impacted by maternal employment are those at the upper percentiles of the weight distribution. When selection on observables is used to assess bias arising from selection on unobservables, maternal employment estimates are determined to be a lower bound, while informal childcare results could be attributed to selection bias. Overall findings are consistent with research from North America and the United Kingdom, and are in contrast to recent findings from the rest of Europe, suggesting the possible role of institutional factors.
Keywords: 330; child overweight; obesity; maternal employment; childcare